Bacterial Transferase MraY, a Source of Inspiration towards New Antibiotics - Fer, Mickaël J.; Corre, Laurent L.; Pietrancosta, Nicolas; Evrard-Todeschi, Nathalie; Olatunji, Samir; Bouhss, Ahmed; Calvet-Vitale, Sandrine; Gravier-Pelletier, Christine (Current Medicinal Chemistry, 2018)
The bacterial resistance to antibiotics constitutes more than ever a severe public health problem. The enzymes involved in bacterial peptidoglycan biosynthesis are pertinent targets for developing new antibiotics, notably the MraY transferase that is not targeted by any marketed drug. Many research groups are currently working on the study or the inhibition of this enzyme. After a concise overview of the role, mechanism and inhibition of MraY, the structure–activity relationships of 5’-triazole-containing aminoribosyluridine inhibitors, we previously synthetized, will be presented. The recently published MraY X-ray structures allowed us to achieve a molecular virtual high-throughput screening of commercial databases and our in-house library resulting in the identification of promising compounds for the further development of new antibiotics.
Keywords: triazoles